(untitled) (Sciences & Technologie. D, Sciences de la terre, 2007)
This paper reviews a certain number of recent empirical studies on social housing design, in relation to some aspects, such as: design quality, standards, health, ecological aspects, energy saving, management, maintenance and repair and competition among designers and developers. Although the subject is complex and in conflict, some practical actions on different levels especialy design seem to lead to partial improvements. Useful recommandations are made as a guidance for future design of social housing programmes.